2009
DOI: 10.1002/bmc.1162
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel HPLC‐MS/MS method for the determination of aconitine and its application to in vitro and rat microdialysis samples

Abstract: A sensitive and selective LC-MS/MS method was developed and validated for the determination of aconitine in microdialysate and rat plasma. Extraction of plasma sample was conducted by use of 1% trichloracetic acid and acetonitrile solution with 10 ng/mL internal standard (propafenone) spiked. Microdialysates were analyzed without sample purification. After sample preparation, 2 microL were injected and separated with an isocratic mobile phase consisting of acetonitrile:0.1% formic acid (60:40, v/v) at a flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The plasma was separated, frozen, and stored at −25°C until assayed. A validated HPLC/MS/MS method was used to determine the aconitine concentration in plasma and dialysis samples (Zhang, et al , ).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The plasma was separated, frozen, and stored at −25°C until assayed. A validated HPLC/MS/MS method was used to determine the aconitine concentration in plasma and dialysis samples (Zhang, et al , ).…”
Section: Methodsmentioning
confidence: 98%
“…Microdialysis probe recovery was calibrated by triplicate measurements of in vitro recovery, delivery and in vivo delivery (Zhang et al , ) Microdialysis probes were placed in a 200 mL beaker containing well‐stirred isotonic PBS (containing Na 2 HPO 4 2.39 g/L, NaH 2 PO 4 9.34 g/L, NaCl 4.79 g/L, pH 5.77) at three different concentrations of aconitine (50, 200 and 500 ng/mL) at 37°C. The probes were perfused with blank isotonic phosphate buffer (pH 5.77) at 2 μL/min and samples of the dialysate were collected at 20 min intervals; aconitine concentrations were analyzed by LC‐MS/MS to give the relative in vitro recovery.…”
Section: Methodsmentioning
confidence: 99%
“…Various alkaloids with properties such as analgesic, anti-inflammatory, antiepileptic, local anesthetic, hypotensive, and spasmolytic activities have been made responsible for their pharmacological effects [3,4]. However, these alkaloids are compounds with cardiotoxic and neurotoxic activities and show a narrow therapeutic index [5,6]. Therefore, the improper use of Aconitum will result in a risk of severe intoxication [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [101] used the microdialysis coupled with the LC-MS/MS technology to determine the aconitine drug concentrations in the rats plasma and in vitro transdermal skin dialysate. In this study and found that the investigation aconitine inter-day and intra-day stability were good, the in vivo recovery of the probe was (34.48 ± 3.05)%.…”
Section: Study the Traditional Chinese Medicine Metabolic Percutaneousmentioning
confidence: 99%